Development of biodegradable solid polymer electrolytes incorporating different nanoparticles for electric double layer capacitor / Chong Mee Yoke - Chong, Mee Yoke (2017)
The increasing demand, rapid consumption of fossil fuels and undesirable consequences of environmental pollution are the alarming concerns from the last few decades. Therefore, much effort has been made to develop biodegradable solid polymer electrolyte (SPE) using natural polymer as host polymer for energy storage and energy conversion devices. The choice of natural polymers as host polymer for the preparation of SPE are hydroxylpropylmethyl cellulose (HPMC) and hydroxylethyl cellulose (HEC). As a result, HEC has been chosen in this study because it has huge amount of hydroxyl groups compared to cellulose and its derivatives. Consequently, it assists in the adsorption of charge carriers, which results in the improvement of charge storage capacity. However, preparation of biodegradable SPE by using solution casting technique exhibits low ionic conductivity. Thus, green ionic liquid (1-ethyl-3-methylimidazolium trifluoromethanesulfonate (EMIMTf)) and nanoparticles (fumed silica (fumed SiO2), copper(II) oxide (CuO) and yttrium(III) oxide (Y2O3)) have been incorporated into the biodegradable SPE along with magnesium trifluoromethanesulfonate (MgTf2) salt as mobile charge carriers to improve its ionic conductivity for electric double layer capacitor (EDLC). Electric double layer capacitor has been chosen over batteries owing to their good thermal and chemical stability, higher potential window (which leads to high energy density) and longer cycling stability. Based on the findings, cell fabricated by inclusion of 2 wt. % of CuO nanoparticles obtained the highest specific capacitance (36.7 F/g) at scan rate of 5 mV/s along with the lowest charge transfer resistance (25.0 Ω) whereas cell fabricated by 2 wt. % of Y2O3 nanoparticles achieved the highest capacitance retention of 91.3 % over 3,000 cycles at current density of 0.4 A/g.